BASIC ASPECTS OF SPAM - Madleňák, Radovan (Doprava a spoje, 2006)
Spam (or "UBE" -- Unsolicited Bulk E-mail), has become a plague for email users around the world. The sheer volume of spam is annoying as users have to clean their inboxes from these unwanted messages on a daily basis. In addition, the aggressive and often sexually explicit nature of spam is offensive and frustrating to most end users. Spam is clearly a nuisance and this article describes some basic aspects and characteristics of spam.